Who Was Shopping More During the Spring Lockdown 2020 in Germany? - Georgiadou, Ekaterini; Koopmann, Anne; Müller, Astrid; Leménager, Tagrid; Hillemacher, Thomas; Kiefer, Falk (Frontiers in Psychiatry, 2021)
Abstract Background: During the lockdown, governmental restrictions resulted in changes to the day-to-day routines of many individuals. Some people appear to cope with stress by panic buying in an attempt to stockpile specific goods, resulting in empty supermarket shelves. Moreover, e-commerce experienced significant growth during this period. We aimed to investigate potential changes in shopping frequencies and preferred shopping type (offline/online) and their relationship with pandemic-specific anxiety and stress during the 2020 spring lockdown in Germany. Methods: To address this question, we assessed self-reported changes in shopping behavior in a German sample via an online survey conducted during April and May 2020. Results: A total of 3122 adults were included in the analysis. Of the total sample, 35 % reported no changes in their shopping behavior, 46.8 % shopped less whilst 18.2 % shopped more during the lockdown. The groups differed in respect of socio-demographic variables and those participants who were shopping more reported greater pandemic-related health fears and stress due to the restrictions. Moreover, they shopped online more often during the lockdown than the other two groups. Conclusion: While the majority of the sample reported no changes in their shopping behavior or even shopped less during the 2020 spring lockdown, a subgroup of individuals was shopping more during this time, especially food and drugstore products. It is important to understand which factors influenced individuals to shop more so that policy makers can target this group and prevent panic buying, especially during subsequent waves of infection. It is also important to inform vulnerable persons about the risk of developing a buying-shopping disorder.